Applications of Metal-Organic Framework Materials. Issue 1 (1st February 2022) - Chai, Wenkui; Shen, Youhong; Wang, Jiahe; Zhang, Geling
Abstract: Metal-organic framework (MOFs) is a new group of porous crystal materials with ultra-high porosity. Its extraordinary surface area, fine and adjustable void surface characteristics and potential industrial-scale scalability make it an attractive target for further research. By searching for the data, we have integrated and summarized the important applications of MOF materials in many fields, such as catalysis, and its enclosed single metal or bimetallic ions provide efficient and synergistic catalytic ability; In adsorption, the special ionic liquid absorbent overcomes the shortcomings of other materials, greatly improves the chemical stability, reduces the corrosivity, and makes the process more environment-friendly and controllable. However, there are still many challenges, and the high cost and complicated preparation process are urgent problems to be solved at present. We need to have a deeper understanding of the growth mechanism of MOF films, improve their quality and thermoelectric stability, and combine them into low-cost polymer films through more reliable theoretical models to eliminate the defects of MOF materials as much as possible. We will continue to pay attention to the development of MOF materials, summarize the advantages of MOF materials, find out the shortcomings, and propose solutions to provide ideas and references for future research.